Sosialisasi Dan Pelatihan Pembuatan Bakso Ikan dan Nugget Ikan Dalam Upaya Meningkatkan Pendapatan Masyarakat Nelayan Pesisr Pantai Di Desa Botutonuo Kecamatan Kabila Bone Kabupaten Bone Bolango - Usman Usman; Lukman Pakaya; Victorson Taruh (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
The percentage of people who are negatively affected financially by the Covid-19 pandemic in Indonesia is very large, so this has an impact on reducing fishermen's household income. Through the service of lecturers who are funded independently, fish preparations, namely fish balls and fish nuggets, will be practiced in an effort to increase the income of households and fishermen groups so that this is a solution and another alternative to increase income and fulfill the nutritional needs of families in Botutonuo Village, Kabila District Bone, Bone Bolango Regency. It is hoped that this can change people's habits to become more productive, namely developing the fish caught by fishermen into products with higher selling value.The aim of implementing this service is a) to increase the income of fishing families and groups and to meet the nutritional needs of fishing families. b). improve skills in processing meatballs and fish nuggets among housewives and young women. This goal can be realized through various solution actions including: (1) mentoring about food and nutrition in general, (2) Counseling about the nutritional composition and benefits of fish, (3) Counseling about various processed fish-based products (4) Training on processing fish into meatballs and fish nuggets and their marketing strategies in an effort to increase the income of the fishing community in Botutonuo Village, Kabila Bone District, Bone Bolango Regency.The method used to achieve this goal is to provide training and assistance to the community by transferring knowledge. This method is to provide knowledge on how to make meatballs and nuggets made from fish, accompanied by methods, techniques and marketing strategies. The target of this training is mothers and young women who are given assistance so that they can have life skills that can increase the income of families and fishing groups as well as provide knowledge about the nutrition found in fish.